Archivists' Information Work Lines: Affective, Information Management, and Hybrid Onsite‐Remote Work Performance. Issue 1 (13th October 2021) - Garwood, Deborah A.; Poole, Alex H.
Abstract: This paper is among the first to investigate information work concepts in the archival context. A qualitative case study, it relies on two rounds of semi‐structured interviews with information professionals at medical history collections in Philadelphia. These interviews bracketed the six months before and after COVID‐19's onset. We analyze three lines of information work that evolved as these archivists shifted the work context to their home environments: affective effort, information management, and hybrid onsite‐remote work performance. Findings suggest that tasks such as processing, digitizing, and curating resources (invisible pre‐pandemic) and reference services (visible pre‐pandemic) overlap in archivists' hybrid onsite‐remote work performance during the pandemic. In recognizing the links between archivists' information work and work performance as a holistic approach to studies of the information‐intensive archival context, this research has implications for the centrality of work context, purpose, and value in the archival context.